2020
DOI: 10.1186/s13638-020-01711-7
|View full text |Cite
|
Sign up to set email alerts
|

Research on DV-Hop improved algorithm based on dual communication radius

Abstract: In order to solve the problem that the traditional DV-Hop location algorithm has a large error in locating unknown nodes, this paper proposes an improved DV-Hop algorithm based on dual communication radius. By adding a communication radius, the algorithm updates the minimum hop number obtained by the unknown node closer to the beacon node to a smaller hop value and keeps the minimum hop number information of unknown nodes farther away. This method reflects the gap between the actual distances in terms of hop n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This section analyzes the performance of the improved sparrow search algorithm with 20 benchmark functions; as shown in Table 2, most of the benchmark functions come from the literatures [20,42]. 3.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This section analyzes the performance of the improved sparrow search algorithm with 20 benchmark functions; as shown in Table 2, most of the benchmark functions come from the literatures [20,42]. 3.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Set the perfect hop count. Suppose the real distance between known nodes i and j is d ij ; the ratio of real distance between known nodes i, j and the maximum communication radius R is defined as the perfect hop count H ij [42]:…”
Section: D-hcssa Localization Algorithmmentioning
confidence: 99%
“…Many researchers put forward different ideas to enhance the localization accuracy of the algorithm: Tang et al used TDOA location feature to quantify the hop value of nodes in DV-Hop location algorithm to achieve a stable effect [ 32 ]. Li et al suggested increasing the communication radius to update the minimum hop-count value of unknown nodes to a smaller hop-count value, which solves the problem that the actual distance difference of the same hop-count value to a certain extent [ 33 ]. Cai et al proposed a new algorithm (N2-3DDV-Hop) to modify the average distance per hop and to optimize the error combined with NSGA-II algorithm [ 31 ].…”
Section: Related Workmentioning
confidence: 99%
“…fit fit P provide sufficient information to narrow the possible locations down to two. An additional circle that passes through the node may narrow the possibilities down to one unique location [17]. The principle of trilateration algorithm is shown in Figure 1 below.…”
Section: Trilateration Algorithmmentioning
confidence: 99%
“…Here, the NN is introduced to predict and correct the ranging error, and then the ABC algorithm is employed to optimize the NN parameters; the distance error was estimated by equation (11) and the prediction error is denoted as △E'. Thus, we have the positioning error correction equation: (17) During the NN-prediction of positioning error, the error of measured distance was determined by connection weights and thresholds. These weight and thresholds were optimized by the ABC algorithm.…”
Section: Error Correctionmentioning
confidence: 99%